Genotypic identification and catechin profiling of Uncaria gambir in West Sumatra, Indonesia - EPI SUPRI WARDI; SUMARYATI SYUKUR; ZULKARNAIN CHAIDIR; JAMSARI JAMSARI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wardi ES, Syukur S, Chaidir Z, Jamsari J. 2024. Genotypic identification and catechin profiling of Uncaria gambir in West Sumatra, Indonesia. Biodiversitas 25: 1151-1158. The primary objective of this study is to assess genetic and chemical variability among four genotypes of Uncaria gambir cultivated in West Sumatra. Uncaria gambir is native to Indonesia, widely cultivated in West Sumatra, used as an herbal remedy, and become a significant agricultural product for Indonesian export with catechin content as a standard. The phytochemical components of this species have been extensively studied, and its extracts are employed in traditional medicine. To fingerprint genomic DNA, we employed three pairs of Specific Sequence-Related Amplified Polymorphism (SRAP) markers selected from 29 combinations tested. A total of 150 amplified bands were generated, highlighting substantial genetic variability among the tested genotypes. Notably, the highest amplified and polymorphic band was obtained with primer E combination from three selected primers (primer E, primer F, and primer T). In addition, only catechins were identified among the four types of catechins employed as HPLC standards. We detected varying catechin concentrations among the genotypes, with genotype Mancik exhibiting the highest concentration. This finding underscores the potential for genotype-specific bioactive marker identification within U. gambir. In addition, this study shows the efficiency of SRAP markers in genotype identification within U. gambir. Furthermore, the identification of catechin as a prominent bioactive marker emphasizes its significance for further exploration and conservation efforts.